Utilizing Technology Management for Effective Cattle Management - Harn, Sai Seng (RSF Conference Series: Business, Management and Social Sciences, 2023)
This research explores the opportunities presented by integrating sensors, big data, and machine learning technology within the global cattle farming industry. The primary objective of this study is to assess the efficacy of technology management in advancing cattle management practices on a global scale. Data was collected from 554 ranchers, with 386 respondents having a minimum of five years of cattle management experience. Rigorous analysis was conducted to examine the impact of technology management, particularly focusing on sensors, big data, and machine learning, on various aspects of effective cattle management. The findings demonstrate the significant importance of technology management and Machine Learning in cattle farming. The study reveals strong correlations between technology management practices and all sub-factors of effective cattle management, including productivity, cost, and health. The research results suggest a substantial positive influence of technology management on enhancing effective cattle management, supported by a 95% confidence level. Furthermore, the study recommends Thailand as an attractive destination for foreign investment in the beef industry, highlighting the pivotal role of artificial intelligence technology in realizing this potential.